HYBRIDISM IN CAMPURSARI MUSIC: AN AESTHETIC STUDY - Ramadhan, Bayu Gilang; Mauliska, Nur; Diamond, Jody (Mozaik : Journal of Art and Architecture, 2024)
Campursari represents a unique fusion between Western diatonic and Javanese pentatonic music. Its inception is rooted in the process of hybridity, a blending of diverse musical elements. In the realm of Indonesian music, "campursari" denotes a genre that integrates various contemporary Indonesian music styles. This study employs qualitative research through a musicological approach, specifically focusing on the aesthetic aspects of campursari music. Hybridity is a defining feature of campursari, setting it apart from other musical forms. This genre is characterized by the combination of disparate musical elements: traditional ethnic instruments such as gamelan, and modern instruments like electric guitars, basses, drums, and keyboards. This blend creates a distinctive hybrid music that emerges from the interplay between Western and traditional musical influences. Campursari artists skillfully merge these elements, resulting in a unique sound that bridges cultural and musical divides. The fusion inherent in campursari not only reflects a blend of different musical traditions but also highlights the genre’s role in evolving contemporary Indonesian music. The aesthetic study of campursari reveals how this hybridization contributes to its dynamic and distinctive musical identity.